Tahfidz Al-Qur'an: A Study of Learning Management Systems in Higher Education - Thontawi, Muhammad; MY, Mahmud; Chaniago, Fransisko; Fiqhi, Ajuzar; Hazairin, Indah Nurul; Afifah, Yuliana (JURNAL AL-TANZIM, 2022)
This study aims to analyze the implementation, evaluation, and management of the tahfidz Al-qur'an program at Ma'had Al-Jami'ah from the State Islamic University of Sulthan Thaha Saifuddin Jambi. The method used in this research is qualitative with a descriptive analysis method. Interviews were conducted directly with the leaders of Ma'had, the tahfidz division, and the mudabbir. The results showed that the management of the Tahfidz Al-Qur'an Program at Ma'had Al-Jami'ah was running well. This program was implemented thanks to the collaboration between the academic community and a facilitator called Mudabbir, who is responsible for optimizing the process of memorizing the Qur'an, and providing a greater understanding of the importance of memorizing the Qur'an for students by adjusting the components of planning, organizing, implementing, and evaluation of the Tahfidz Al-qur'an Program. Ma'had Al-jami'ah continues to make adjustments to improve the quality of graduates and equip them with a deep understanding of the meaning of the Qur'an to increase students' faith and piety.